PENGEMBANGAN BAHAN AJAR DENGAN PENDEKATAN KONTEKSTUAL PADA MATERI KUBUS DAN BALOK UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS DAN PEMECAHAN MASALAH SISWA KELAS VIII SMP ISS JATIPURNO WONOGIRI DEVELOPING TEACHING MATERIALS USING CONTEXTUAL APPROACH IN CUBE AND CUBOID MATERIAL TO IMPROVE STUDENT’S MATHEMATICAL CONNECTION AND PROBLEM SOLVING FOR GRADE VIII JUNIOR HIGH SCHOOL ISS JATIPURNO WONOGIRI - Ani Kusniawati; Sugiyono Sugiyono (Jurnal Pedagogi Matematika, 2016)
Abstrak Penelitian pengembangan ini bertujuan untuk mengembangkan bahan ajar berupa LKS dengan menggunakan pendekatan kontekstual  pada materi kubus dan balok serta mengetahui kualitas LKS ditinjau dari kevalidan, kepraktisan, dan keefektifan.  Pengembangan dilakukan berdasarkan model ADDIE. Instrumen yang digunakan berupa lembar penilaian LKS untuk ahli materi dan ahli media, angket respon siswa dan guru, serta tes kemampuan koneksi matematis dan  pemecahan masalah. LKS telah diujicobakan di SMP ISS Jatipurno, Wonogiri pada tanggal 11-23 Mei 2015. Berdasarkan hasil penilaian LKS oleh ahli materi dan ahli media, diperoleh rata–rata skor berturut-turut sebesar 4,2 dan 4,43  dengan kriteria “valid” dan “sangat valid”. Berdasarkan hasil angket respon siswa dan guru, diperoleh rata-rata skor berturut-turut sebesar 3,64 dan 4,43  dengan kriteria “praktis” dan “sangat praktis”. Hasil tes kemampuan koneksi matematis  dan kemampuan pemecahan masalah menunjukkan  persentase ketuntasan klasikal siswa berturut-turut sebesar 73,17%  dan 70,43%  dengan kriteria "efektif".  Dengan demikian, LKS yang dihasilkan dinyatakan valid, praktis, dan efektif.  Kata Kunci: pendekatan kontekstual, kemampuan koneksi matematis, kemampuan pemecahan masalah, kubus, balok  Abstract This study aimed to  developing teaching material as student worksheets using contextual approach in cube and cuboid materials and describing the quality of student worksheets in terms of validity, practicality, and effectivity.The development of student worksheets  referred to ADDIE model. The instruments used in this research were validation questionnaire for materials expert and media expert, questionnaire responses of student and teacher, and mathematical connetion and problem solving test. Student worksheets as the product of this study had been implemented in ISS Junior High School Jatipurno, Wonogiri at May, 11 2015 until May, 23 2015. Based on the result of validation questionnaire by the materials expert obtained an average score 4,2 was “valid” criteria. Based on the result of validation questionnaire by the media expert obtained an average score 4,43 was “valid” criteria. Based on the result of the questionnaire responses of student obtained an average score 3,64 was “valid” criteria. Meanwhile, the result of the questionnaire responses of teacher obtained an average score 4,43 was “very practice” criteria. Analysis of the mathematical connection test showed that the classical completeness percentage was 73,17%, and analysis of the problem solving test showed that the classical completeness percentage was 70,43%, means that they were “effective” criteria. So that, this student worksheets were valid, practice, and effective.  Keywords:contextual approach, mathematical connection, problem solving, cube, cuboid